An evaluation of the elastic recovery of nickel titanium archwires following ligation in palatally-displaced lateral incisors - Finan, Leah (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2023)
Introduction The levelling and aligning phase of orthodontic treatment involves the use of low-modulus nickel titanium archwires with small cross-sectional diameters. Aims and objectives The aim of this study was to compare permanent deformation associated with a range of superelastic 0.012" and 0.014" nickel titanium archwires following ligation in a simulated set up. Furthermore, the study was designed to compare the maximum force imparted by these archwires at a variety of magnitudes of tooth displacement. Materials and methods 3D-printed models were created of a typodont with the lateral incisor palatally displaced (3-, 4- or 5- mm). The models incorporated conventional brackets, into which the archwires were ligated. A total of 288 archwires from two brands (Euroform (EO) and American Orthodontics (AO)) of two cross sectional diameters (0.012" and 0.014") were tested for plastic deformation. This deformation was measured objectively using linear and angular measurements and subjectively using a validated index created to categorise archwires based on the degree of deformation and their clinical usability. 3"point bending tests were used to examine the load deflection characteristics of a sample of 72 archwires from the same 36 batches used in the typodont component of the study and determine the maximum and unloading force generated at archwire displacements of 3-, 4- and 5- mm. Results Shapiro-Wilk normality tests showed the majority of the data collected for Part I was not normally distributed so therefore non-parametric Kruskal-Wallis testing was used. EF archwires had lower distortion compared to AO archwires (P = 0.008). There was no statistically significant difference in deformation noted between 0.012" EF and AO archwires (P = 0.89). However, the 0.014" EF archwire had significantly lower deformation than AO archwires (P = <0.001). A wide variation in force levels at maximum archwire displacement was observed, influenced by archwire size and type, but with differences also noted within wire batches. Using independent samples Mann-Whitney U Tests, the mean force produced by the 0.012" archwires was significantly less than that produced by the 0.014" archwires at 3-, 4- and 5- mm displacements. The mean force produced by the AO archwires was significantly less that for the EF archwires at the same magnitudes of displacement for both 0.012" and 0.014" sizes. Conclusions Based on this artificial set-up, the use of an 0.012? archwire for tooth displacements of 3 mm or more may be considered in order to permit the delivery of lighter forces. EF archwires underwent a lesser degree of deformation than AO archwires. A high degree of variability in the performance of narrow dimension nickel titanium archwires can be expected and is influenced by manufacturer, archwire dimension and the degree of tooth displacement. Moreover, susceptibility to deformation appear to vary within batches of identical wires.
APPROVED
Keywords: Orthodontics; Archwires; Nickel titanium; Archwire deformation